CA3 excitatory synapse loss as a chronic effect of septic shock in middle‐aged mice. (1st February 2022) - Manabe, Tatsuya; Rácz, Ildikó; Schwartz, Stephanie; Santarelli, Francesco; Emmrich, Julius V.; Neher, Jonas J.; Heneka, Michael T.
Abstract: Background: Septic encephalopathy represents an acute cerebral dysfunction following systemic inflammation by pathogens. Notably, more than 70% of sepsis survivors present this disorder years after the hospital discharge (Widmann and Heneka, 2014). In rodents, septic shock can be modelled by an intraperitoneal injection of lipopolysaccharide (LPS), and our previous findings indicate that LPS can lead to neuronal loss and synaptic destruction accompanied by glial activation (Semmler et al., 2007; Weberpals et al., 2009; Tejera et al., 2019). However, it remains elusive what ultimately drives this cognitive impairment and how neuroinflammation contributes to these cerebral changes. Method: We intraperitoneally injected 1.5 mg/kg LPS on two consecutive days in mice at 14 months of age. Two different serotypes of LPS ( Salmonella enterica and E. coli O55:B5) were compared. The brains were biochemically and histologically analysed at 7 or 63 days post‐injection (dpi) in order to study cytokine levels, microglia morphology, neuron/synapse loss and synaptic pruning by microglia. To quantify number of synapses and synaptic pruning, synaptic puncta were visualised by a super‐resolution microscope with an Airyscan detector. Result: Proinflammatory responses to septic shock were detected at 7 dpi, including elevated cytokines and the less ramified morphology of microglia. These changes were mostly normalised at 63 dpi, except a persisting high IL‐6 level. Neuron density in the hippocampus was found to be normal at 7 dpi and 63 dpi. However, excitatory synapses and synaptic complement factor C3 were reduced in the CA3 at 63 dpi. Similar changes were not obtained at 7 dpi and in other subfields (CA1 and DG). Moreover, the engulfed synaptic puncta density inside CA1 and CA3 microglia lysosomes remained normal at 7 dpi and 63 dpi. Conclusion: Neuroinflammation elicited by systemic LPS injection was mostly resolved at 63 dpi, while the IL‐6 level remained elevated. Whereas the hippocampal neurons were intact, the excitatory CA3 synapses were locally reduced by 63 dpi in a manner independent of microglial synaptic pruning. We postulate this synapse loss might be associated with the long‐lasting cognitive impairments of sepsis survivors.